Preparation and characterization of aceclofenac microspheres - Trivedi, Parul; Verma, A M L; Garud, N (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present study was to microencapsulate the anti-inflammatory drug (aceclofenac) to provide controlled release and minimizing or eliminating local side effect by avoiding the drug release in the upper gastrointestinal track. The drug was targeted to the colon and their aligned area for their local effect. Aceclofenac was microencapsulated with Eudragit (S 100, RL 100, and RS 100), using an O/W emulsion-solvent evaporation technique. Aceclofenac microspheres were subjected to micromeritic properties including angle of repose, bulk density, tapped density, Carr’s index, Hausner’s ratio, and particle size determination. Microspheres were subjected to drug loading, in vitro drug release as well as for scanning electron microscopy.The prepared microspheres were white, free-flowing, and almost spherical in shape.The drug- loaded microspheres show 60-82% drug entrapment, angle of repose was in the range of 16.13 ± 0.621-24 ± 0.590, bulk and tapped densities respectively were in the range of 0.311 ± 0.006-0.562 ± 0.012 and 0.373 ± 0.01-0.735 ± 0.02, Carr’s index ranges from 14.04 ± 0.026 to 27.25 ± 1.405, Hausner’s ratio was 1.14 ± 0.026-1.37 ± 0.03, and particle size was in the range of 79.7016-144.840 μm. In vitro drug release studies were carried out up to 24 h in three different pH media, i.e., 0.1 N HCl (pH 1.2), phosphate buffer (pH 6.8), and phosphate buffer (pH 7.4). The drug-polymer concentration of dispersed phase influences the particle size and drug release properties. All the formulations at higher pH were followed by the Matrix-Higuchi model.